Analyzing Presidential Discourse on the Paris Agreement: Trump’s Skepticism vs. Jokowi’s Support - Sitti Zarina Alimuddin; Ali Maksum (Universitas Muhammadiyah Yogyakarta, 2023)
This research analyzes President Trump and Jokowi’s speeches on the Paris Agreement. The descriptive qualitative approach was employed in this study. The Critical Discourse Analysis model examines the connections among language, ideology, and power. Van Dijk’s Discourse Analysis Model was used in critical discourse analysis to examine President Trump’s speech. NVivo 12 was further utilized to gather and evaluate the data. The study highlighted a significant contrast in how presidents handle the Paris Agreement. Despite a lack of factual evidence, Trump tried to amplify the perception that the United States is unfairly targeted in environmental efforts, while President Jokowi supported and favored the agreement. Through discourse analysis, the stance of political leaders and public opinion could influence the acceptance of the Paris Agreement.